2019
DOI: 10.3390/w11071376
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Macroinvertebrate Community in Dryland Streams: The Case of the Tehuacán-Cuicatlán Biosphere Reserve (México) Facing Climate Change

Abstract: The Tehuacán-Cuicatlán Biosphere Reserve (TCBR), the southernmost semi-arid zone of North America, includes two dryland streams, the Río Salado (RS) and Río Grande (RG); it is surrounded by high vegetation diversity, a cacti diversification center, and the densest columnar cacti forest worldwide. However, no scientific knowledge is currently available on these dryland streams. We evaluated water quality, its relationship with the local geological characteristics, land uses, and the composition of aquatic macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Despite the relatively low diversity and poor habitat conditions in the Extoraz River, we identified 32 different taxa (mostly at family level). By comparison, López-López et al 42 found 40 macroinvertebrate families in the Salado River, which flows across another Mexican PNA with similar vegetation, using the same sampling methods. However, in the Salado River, studies were conducted in two sampling sites, whereas our study was conducted in four study sites (Extoraz River).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively low diversity and poor habitat conditions in the Extoraz River, we identified 32 different taxa (mostly at family level). By comparison, López-López et al 42 found 40 macroinvertebrate families in the Salado River, which flows across another Mexican PNA with similar vegetation, using the same sampling methods. However, in the Salado River, studies were conducted in two sampling sites, whereas our study was conducted in four study sites (Extoraz River).…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the entry of clean water, where greater diversity is related to higher values of physicochemical parameters such as dissolved oxygen, water temperature, and transparency [59]. Different studies have described significant differences and important changes from the upper to the lower basin in the aquatic macroinvertebrate taxa, which could be related to changes in the physicochemical characteristics of the water by wastewater inputs, changes in habitats, and physical modifications to the channel, including nearby roads [60][61][62]. The values of the BMWP and the % EPT-B indices better reflected the general quality of the river, an aspect also described in other studies [45,[63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Variables such as chlorides, conductivity, and total hardness can bring down the WQI scores, as pointed out by López-López et al (2019), who recorded low WQI scores in a river with high values of these parameters. Maansi et al (2022), estimating various water quality indices in Lake Sukhna, in India, found that higher hardness and alkalinity influenced the water quality.…”
Section: Water Quality Indexmentioning
confidence: 96%